Extent of Awareness Regarding Natural Resource Management Among Rural Women in Shahdol District of M.P. - Uttam Singh Bagri , Kinjulck C Singh and C J Singh, (Indian Journal of Extension Education, 2016)
A research on awareness of rural women was conducted during 2011 - 2012 to know their extent of awareness regardingNatural Resource Management. Six villages of Shahdol district of Madhya Pradesh province were selected as study area.A sum of 120 women was selected as respondents using equal proportion method. The data was collected throughstructured, pretested interview schedule. The study confirms that most of the respondents had medium level of knowledgeregarding ITK of Natural Resource Management and high extent of awareness regarding management of naturalresources . Education, social participation, type of family, land holding, mass media exposure, attitude towards naturalresource management were found to have significant association with extent of awareness regarding natural resourcemanagement at 0.005 level of significance whereas ITK regarding natural resource management was found to havesignificant association at 0.01 level of significane. They should be motivated to practice and participate more in suchactivities.